Radiation therapy and the risk of herpes zoster in patients with cancer. Issue 15 (15th May 2020) - Shimizuguchi, Takuya; Sekiya, Noritaka; Hara, Konan; Taguchi, Ayumi; Nakajima, Yujiro; Miyake, Yu; Shibata, Yukiko; Taguchi, Kentaro; Ogawa, Hiroaki; Ito, Kei; Karasawa, Katsuyuki
Abstract : Background: The role and impact of radiation therapy (RT) on the development of herpes zoster (HZ) has not been well studied. The objective of this study was to investigate the association between RT and HZ. Methods: A propensity score‐matched, retrospective cohort study was conducted using institutional cancer registry data and medical records from 2011 to 2015. The risk of developing HZ in the RT and non‐RT groups was compared using a Cox proportional hazards model. Associations also were explored between the RT field and the anatomic location of HZ in patients who developed HZ after RT. The expected number of HZ events within the radiation field was calculated according to the RT received by each patient; then, this number was compared with the observed number of in‐field events. Results: Of 17, 655 patients, propensity score matching yielded 4350 pairs; of these, 3891 pairs were eligible for comparison. The cumulative incidence of HZ in the RT group (vs the non‐RT group) during the first 5 years after the index date was 2.1% (vs 0.7%) at 1 year, 3.0% (vs 1.0%) at 2 years, 3.4% (vs 1.3%) at 3 years, 4.1% vs 1.7% at 4 years, and 4.4% vs 1.8% at 5 years. The RT group showed a significantly higher risk of HZ than the non‐RT group (hazard ratio, 2.59, 95% CI, 1.84‐3.66). In the 120 patients who developed HZ after RT, HZ events were observed significantly more frequently within the RT field than expected (74 vs 43.8 events; P  < .001). Conclusions: Patients with cancer who received RT showed a significantly higher risk of HZ, which was commonly observed within the radiation field. Abstract : The role and impact of radiation therapy on the development of herpes zoster have not been well studied. This study demonstrates an increased risk of herpes zoster development among patients with cancer who receive radiation therapy, especially within the radiation field.